Fracture characterization of low-permeability oil reservoirs under hydrofracturing and fracturing-flooding processes under varying in-situ stress conditions - Li, XiaoShan; Li, Kai; Yang, Shuguang; Luo, Qiang; Liu, JiaXing; Shi, GuoXin (Frontiers in Earth Science, 2025)
Enhancing the efficient development of these low-permeability and ultra-low-permeability sandstone oil reservoirs is an important support for maintaining and increasing production in Xinjiang Oilfield. To explored the morphological characteristics of fractures created by fracturing-flooding, The true three-axis hydraulic fracturing and the equivalent hydraulic model in PFC2D were adopted. The result shows that with the increase of in situ stress, due to the capillary action, the corresponding flow rate for the fracture becomes lower. At the same time, the in situ stress inhibits the expansion of the fracture cracks. The distance that the cracks extend along the vertical principal stress direction gradually also decreases with the increase of in situ stress, while the area of micro-damage around the fracturing holes gradually increases. During the fracturing-flooding process, acoustic emissions will be generated, combined with the CT scan results, it can be obtained that fracturing-flooding will cause micro-damage around the fracture hole. And, the in situ stress magnitudes will also be conducive to the formation of micro-damage around the fracture holes.